2005
DOI: 10.1002/fut.20180
|View full text |Cite
|
Sign up to set email alerts
|

A contango-constrained model for storable commodity prices

Abstract: This article presents a model of commodity price dynamics under the riskneutral measure where the spot price switches between two distinct stochastic processes depending on whether or not inventory is being held. Specifically, the drift of the spot price is equal to the cost of carry when the stock is positive. Conversely, whenever the drift of the spot price is less than the cost of carry, no inventory is being held.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Others such as Ribeiro and Hodges (2004) have suggested that during times of comfortable supply, when injections into storage increase, speculators will require lower premia in their expected returns, so risk will be priced more cheaply as inventory increases. We, on the other hand, argue that it is deviations from expected seasonal storage that producers take into account.…”
Section: Spot Prices Forward Curves Risk Premia and Convenience Yieldmentioning
confidence: 99%
“…Others such as Ribeiro and Hodges (2004) have suggested that during times of comfortable supply, when injections into storage increase, speculators will require lower premia in their expected returns, so risk will be priced more cheaply as inventory increases. We, on the other hand, argue that it is deviations from expected seasonal storage that producers take into account.…”
Section: Spot Prices Forward Curves Risk Premia and Convenience Yieldmentioning
confidence: 99%
“…Furthermore, the economic model precludes carry (cash) arbitrage. This is not the case for the reduced form pricing models, as noted by Ribeiro and Hodges (). For natural gas, precluding carry arbitrage appears relevant to produce an empirically relevant asymmetric basis as a function of storage (working curve).…”
Section: Introductionmentioning
confidence: 91%
“…However, as stated by Postali and Picchetti (2006), one difficulty with many of these models is that they included state variables, such as the convenience yield, which are not directly observable and thus are to be estimated. Furthermore, many of these models do not guarantee that the convenience yield is always positive and thus possibly allow arbitrage opportunities (see Ribeiro and Hodges 2005). Generally, the main costs of extensions to multifactor models are the growing number of parameters to be estimated and the need for numerical solutions in many cases.…”
Section: Introductionmentioning
confidence: 98%
“…In general, as stated by Ribeiro and Hodges (2005), reduced-form models dominate the literature and practice on energy derivatives. They are especially attractive from the practitioners' perspective when they provide closed-form solutions to evaluate futures and other derivatives which in turn facilitate calibration and computational implementation of the models.…”
Section: Introductionmentioning
confidence: 99%